Effective Model in Financial Services Marketing in Tehran Stock Exchange - ghasem ansaari ranani; vahid nasehi far (مطالعات مدیریت بهبود و تحول, 2007)
By developing the global condition and changing the Industrial Economy to Service Economy, and also considering the fast development of organizations and service institutions in all over the world,a new field of marketing as called, "Services Marketing" has been introduced. Different professional branches of service marketing such as "Financial Services Marketing: in financial institutions and financial dealing have been practiced. Considering the importance and implication of financial services marketing in the development of stock exchange market , We have reviewed this issue in the present research. This study is a survey related with applying the context , methods and financial services marketing models in Tehran stock exchange market. Regarding the research literature, marketing model of dealing services are as follow: l. Marketing Mixes , 2.Marketing research in the field of assessing self-potentiality, knowing the competitors, investors and environmental conditions, 3.Market segmentation, its